THE KSPM PROGRAM GOES TO ORMAWA FOR CAPITAL MARKET LITERACY AND EDUCATION - Tine Badriatin; Linda Septiana; Lucky Radi Rinandiyana (Universitas Muhammadiyah Mataram, 2019)
Abstrak: Pengabdian pada masyarakat melalui sosialisasi dan edukasi serta literasi pasar modal ini bertujuan untuk menambah partisipasi masyarakat berinvestasi di pasar modal khususnya di kalangan civitas academika Universitas Siliwangi. Kegiatan ini diikuti oleh 30 peserta yang mana 20 peserta berasal dari ORMAWA Fakultas Keguruan dan Ilmu Pendidikan Jurusan Pendidikan Ekonomi Universitas Siliwangi. Kegiatan ini dilaksanakan melalui metode diskusi dan tanya jawab daripada peserta yang dilaksanakan dengan 2 materi dalam satu hari kegiatan. Namun demikian kegiatan ini perlu ditindak lanjuti kembali dimana dengan kegiatan lanjutan literasi pasar modal ini peserta memiliki antusias yang tinggi untuk memperluas wawasan mengenai pasar modal serta perlu diperluas kembali sasaran atau target dari kegiatan sosialisasi dan edukasi pasar modal ini. Abstract: Community service through socialization and education as well as capital market literacy aims to increase public participation in investing in the capital market, especially among the Siliwangi University academic community. This activity was attended by 30 participants, of which 20 participants came from the ORMAWA Faculty of Teacher Training and Education, Department of Economic Education, Siliwangi University. This activity was carried out through the method of discussion and question and answer than participants who carried out with 2 materials in one day of the activity. However, this activity needs to be followed up again where with the continued activity of capital market literacy, participants have a high enthusiasm to broaden their horizons about the capital market and also need to expand the targets or targets of this capital market education and education socialization activity.